(untitled) (Legal journal - Research in Legal and Social Sciences, 2017)
Every public institution needs to develop a sense of belonging in its human talents in order to install knowledge of the vision, mission and strategic objectives to achieve the commitment and identification of officials with the organization, in order to provide a quality service to citizens. A quality public service with sensitive and effective attention will satisfy citizen expectations regarding the services provided by public officials in the performance of their duties. The sense of belonging is built collectively among all the components of a public institution. The success of an institution in fulfilling its purposes, the achievements obtained, the challenges assumed and the work responsibility, is based on the authentic commitment of participation of the officials, managers and leaders, which contributes to promote the sense of belonging among all members of the organization. The purpose of the research is to identify the factors that affect the sense of belonging among the officials of the Training Center of the Public Ministry, analyze whether this value has been developed and propose actions aimed at strengthening the sense of belonging in the Public Ministry. .